Increased rates of parental separation and anxiety among Latinx youth. (September 2020) - Brown, Calla R.; Shramko, Maura; Garcia-Huidobro, Diego; Miller, Kathleen K.; Brar, Pooja; Ogugua, Fredrick; Svetaz, Maria Veronica
Highlights: Rates of youth reporting ever experiencing parental separation were steady between 2009 and 2016 but increased in 2017. The number of visits seen with a diagnosis of anxiety also increased during the study period, rising to three times higher. Youth reporting parental separation were older. Parental separation was not significantly associated with visits with an anxiety diagnosis once we adjusted for patient age. Abstract: Family separation during the immigration journey and its effects on the health of affected children and adolescents is a growing concern in the United States. Anti-immigrant policies are also on the rise, creating a negative context for development. Young people seen at a clinic-based Latinx youth development program completed intake questionnaires between 2009 and 2018 (n = 824). These, along with diagnoses coded at each visit, were used to examine the prevalence and associations between parental separation, demographics, and the number of visits with diagnoses of anxiety and depressive mood disorders, respectively. Bivariate associations were tested, and then regression was used to examine if parental separation was associated with the number of visits with an anxiety diagnosis. Rates of youth reporting ever experiencing parental separation were steady between 2009 and 2016 (range 3.1–9.0%) but increased in 2017 to 22.7%. The number of visits seen with a diagnosis of anxiety also increased during the study period, rising to three times higher. Youth reporting parental separation were older, and patient age was positively associated with the number of visits with an anxiety diagnosis; however, parental separation was not significantly associated with visits with an anxiety diagnosis once we adjusted for patient age. While further research is needed to explore the relationship between parental separation and anxiety disorders, this research sheds light into the significant increase of anxiety of the Latinx youth studied.